Analysis of clinical outcomes according to original treatment groups 16 years after the pivotal IFNB-1b trial. Issue 8 (19th June 2010) - Ebers, G C; Traboulsee, A; Li, D; Langdon, D; Reder, A T; Goodin, D S; Bogumil, T; Beckmann, K; Wolf, C; Konieczny, A; ,
Abstract : Background: Evidence for efficacy of disease-modifying drugs in multiple sclerosis (MS) comes from trials of short duration. We report results from a 16 y, retrospective follow-up of the pivotal interferon β-1b (IFNB-1b) study. Methods: The 372 trial patients were randomly assigned to placebo (n=123), IFNB-1b 50 μg (n=125) or IFNB-1b 250 μg (n=124) subcutaneously every other day for at least 2 y. Some remained randomised for up to 5 y but, subsequently, patients received treatment according to physicians' discretion. Patients were re-contacted and asked to participate. Efficacy related measures included MRI parameters, relapse rate, the Expanded Disability Status Scale, the Multiple Sclerosis Functional Composite Measure and conversion to secondary progressive MS. Results: Of the 88.2% (328/372) of patients who were identified, 69.9% (260/372) had available case report forms. No differences in outcome between original randomisation groups could be discerned using standard disability and MRI measures. However, mortality rates among patients originally treated with IFNB-1b were lower than in the original placebo group (18.3% (20/109) for placebo versus 8.3% (9/108) for IFNB-1b 50 μg and 5.4% (6/111) for IFNB-1b 250 μg). Conclusions: The original treatment assignment could not be shown to influence standard assessments of long-term efficacy. On-study behaviour of patients was influenced by factors that could not be controlled with the sacrifice of randomisation and blinding. Mortality was higher in patients originally assigned to placebo than those who had received IFNB-1b 50 μg or 250 μg. The dataset provides important resources to explore early predictors of long-term outcome.